STRATEGI PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL (KAT) SUKU BONAI DI KABUPATEN ROKAN HULU - ", Mayliza; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Isolated traditional community (ITC) is one of the issues in Indonesia and as issues andchallenge for local government one of the them Rokan Hulu districts. The number of ITC’speople is still quite large. They are scattered throughout the geographic locations which arerelatively difficult to reach and in general, they are lagged behind economically,socially andpolitically in comparison with the orther citizens. At once, ITC’s people are a part the citizenswho have the same obligations and rights as the other citizens to participate in development andto enjoy the results of such development through districts Rokan Hulu.Through communityempowerment of ITC’s be responsibility from local government. Social service form women’sempowerment and child protection be in charge implementation ITC’s of empowerment bonaitribe programs. Expected to be able to help them out from border and inland life to wards abetter life. This study is the study of literature taken from various existing references. Then, thedata were packed and explored as the data and information to give idea overview of strategysocial service for women’s empowerment and child protection Rokan Hulu districts. The purposeof this study was to find out how importance strategy in ITC’s empowerment bonai tribe.Strategy in empowerment is a way by utilizing the resources they have and opportunities indealing with weaknesses and hands in ITC’s empowering.Keywords:Isolated Traditional Community (ITC),Empowerment,Strategy